Branding of Sports Tourism Destination in Mashhad City - Ahmad Nazari Torshizi; Zahra Hemmat Yar; Javad Gholamian; Ahmad Mahmoudi; Sahar Pirjamadi (Research in Sport Management and Marketing)
Purpose: Today, there are sizable chunk of cities in the world, trying to introduce themselves as destination brands in various areas. Given that, this study aimed to explain the effective factors on destination branding in the field of sports tourism in Mashhad. Method: This study was of applied research, from the view point of purpose, and also, in terms of its nature, it was in the field of exploratory research, furthermore, in terms of data collection, it was of a descriptive-survey type. Also, due to the use of Q methodology, it was a type of mixed research (quantitative-qualitative). The statistical population included marketing and branding specialists, sports tourism experts, sports management professors and people active in the field of tourism who had complete knowledge of Mashhad. For this purpose, theoretical saturation was achieved after in-depth and semi-structured interviewing 16 experts selected purposefully and finally 26 people completed the Q questionnaire. Results: The data obtained from sorting the Q statements were entered into SPSS software version 26 and analyzed through varimax rotation (exploratory factor analysis). The priority of these models were infrastructural factors, inner city situation, cultural activities, commercial creativities, urban essence, and transportation, respectively. Conclusion: The results of this research emphasize the strengthening of indicators such as suitable access to the Internet, managerial decisions, cultural diversity, the existence of suitable places and markets, the potential of the region and the smoothness of traffic and roads in order to make the destination as a brand in Mashhad's sports tourism.